2021
DOI: 10.3389/fpsyg.2021.671615
|View full text |Cite
|
Sign up to set email alerts
|

Validating the General Extended Technology Acceptance Model for E-Learning: Evidence From an Online English as a Foreign Language Course Amid COVID-19

Abstract: The present study validated the general extended technology acceptance model for e-learning (GETAMEL) with the survey data from the English as a foreign language (EFL) online class during the novel coronavirus lockdown period. A total of 678 undergraduates participated in the survey. Structural equation modeling was employed to analyze the data. The results showed that the influence of perceived usefulness of students on their intentional behavior to use the online learning system was not mediated by their att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 61 publications
5
21
0
Order By: Relevance
“…Research also indicated that students who assumed blended learning to be useful for their education would be more likely to adopt it (Tselios et al, 2011 ). Such a result indicates that it is important for instructors to understand students’ attitudes toward technologies in online or blended learning, especially when dealing with different situations, such as under the influence of COVID-19 (Jiang et al, 2021 ) and help students to build a positive belief in blended learning at the early stage of learning. Effective strategies include the use of lectures or social influences to help students understand the potential advantages of blended learning and the presentation of successful blended learning courses to students.…”
Section: Discussionmentioning
confidence: 99%
“…Research also indicated that students who assumed blended learning to be useful for their education would be more likely to adopt it (Tselios et al, 2011 ). Such a result indicates that it is important for instructors to understand students’ attitudes toward technologies in online or blended learning, especially when dealing with different situations, such as under the influence of COVID-19 (Jiang et al, 2021 ) and help students to build a positive belief in blended learning at the early stage of learning. Effective strategies include the use of lectures or social influences to help students understand the potential advantages of blended learning and the presentation of successful blended learning courses to students.…”
Section: Discussionmentioning
confidence: 99%
“…Two professors in the field of educational technology were consulted to ensure the surface validity of the three pairs. Following Jiang et al’s method [ 40 ], a filtering criterion was applied in the data preprocessing stage to exclude those whose responding performance was inconsistent. To be exact, if the sum of the absolute value of the averaged difference between all the three filtering pairs was greater than 1 unit per pair, then the responding performance of the participant was defined as inconsistent, and thus the corresponding data record was considered invalid for further analysis and should be removed from the sample.…”
Section: Methodsmentioning
confidence: 99%
“…PR of medical AI technologies measures how the AI technologies are able to enhance medical students’ productivity or performance. In literature pertaining to technology adoption, a plethora of primary studies have obtained positive evidence of the positive impact of attitude on behavioral intention [ 40 , 41 ]. Because it is considered a factor which behavioral studies commonly employ as an estimate of attitude toward behavior, PR is oftentimes considered as an antecedent of BI [ 42 ].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that examined the potential relation between PEOU and PU in the domain of online learning has shown that PEOU of online learning positively affected the learners' PU of online learning (Almarabeh, 2014;Al-Okaily, Alqudah, Matar, Lutfi, & Taamneh, 2020;Farahat, 2012;Hsieh, Huang, & Wu, 2016;Jiang et al, 2021). While previous research has shown a significant relationship between learners' PEOU of online learning and their attitudes towards using online learning (Almarabeh, 2014;Farahat, 2012;Jiang et al, 2021), learners' PEOU of using online learning in the study of Natasia, Wiranti, & Parastika, (2022) did not significantly affect the learners' attitudes towards using online learning system.…”
Section: Literature Reviewmentioning
confidence: 99%